First Report of Sorafenib in Patients With Acute Myeloid Leukemia Harboring Non-Canonical FLT3 Mutations - Daver, Naval; Price, Allyson; Benton, Christopher B.; Patel, Keyur; Zhang, Weiguo; Konopleva, Marina; Pemmaraju, Naveen; Takahashi, Koichi; Andreeff, Michael; Borthakur, Gautam (Frontiers in Oncology, 2020)
The prognostics implications of patients with acute myeloid leukemia harboring non-canonical FLT3 is unknown. The use of tyrosine kinase inhibitors in this patient population has not been previously reported. We report successful targeted therapy against non-ITD, non-D835 driver FLT3 alterations in two patient case studies with acute myeloid leukemia.